A highly robust metal–organic framework based on an aromatic 12-carboxyl ligand with highly selective adsorption of CO2 over CH41. Issue 46 (11th June 2015) - He, Hongming; Song, Yang; Zhang, Chuanqi; Sun, Fuxing; Yuan, Rongrong; Bian, Zheng; Gao, Lianxun; Zhu, Guangshan
<x xml:space="preserve">Abstract</x> A stable microporous anionic MOF based on a dendritic aromatic 12-carboxyl ligand was synthesized, which demonstrates high Qst for CO2 and highly selective gas adsorption of CO2 over CH4.